2a(3a+4)+6a(2A+1)=

Simple and best practice solution for 2a(3a+4)+6a(2A+1)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2a(3a+4)+6a(2A+1)= equation:


Simplifying
2a(3a + 4) + 6a(2A + 1) = 0

Reorder the terms:
2a(4 + 3a) + 6a(2A + 1) = 0
(4 * 2a + 3a * 2a) + 6a(2A + 1) = 0
(8a + 6a2) + 6a(2A + 1) = 0

Reorder the terms:
8a + 6a2 + 6a(1 + 2A) = 0
8a + 6a2 + (1 * 6a + 2A * 6a) = 0
8a + 6a2 + (6a + 12aA) = 0

Reorder the terms:
8a + 6a + 12aA + 6a2 = 0

Combine like terms: 8a + 6a = 14a
14a + 12aA + 6a2 = 0

Solving
14a + 12aA + 6a2 = 0

Solving for variable 'a'.

Factor out the Greatest Common Factor (GCF), '2a'.
2a(7 + 6A + 3a) = 0

Ignore the factor 2.

Subproblem 1

Set the factor 'a' equal to zero and attempt to solve: Simplifying a = 0 Solving a = 0 Move all terms containing a to the left, all other terms to the right. Simplifying a = 0

Subproblem 2

Set the factor '(7 + 6A + 3a)' equal to zero and attempt to solve: Simplifying 7 + 6A + 3a = 0 Solving 7 + 6A + 3a = 0 Move all terms containing a to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + 6A + -7 + 3a = 0 + -7 Reorder the terms: 7 + -7 + 6A + 3a = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 6A + 3a = 0 + -7 6A + 3a = 0 + -7 Combine like terms: 0 + -7 = -7 6A + 3a = -7 Add '-6A' to each side of the equation. 6A + -6A + 3a = -7 + -6A Combine like terms: 6A + -6A = 0 0 + 3a = -7 + -6A 3a = -7 + -6A Divide each side by '3'. a = -2.333333333 + -2A Simplifying a = -2.333333333 + -2A

Solution

a = {0, -2.333333333 + -2A}

See similar equations:

| -13w+w^2=0 | | 8x-17=23 | | -x(6+3-2)=x(2+4)+8 | | -14+x=33 | | 9(x-2)+6(x-3)=0 | | 5x+10y=5750 | | 5x(3x+2y)= | | 6(2x-5)-5x=2x-7+2 | | -9x+2x= | | 3(4x-2)=-42 | | -2x+3(-x+4)=0 | | 4(-2x-3)=-44 | | -9x+2x-7= | | -4(-2+3n)=44 | | y=2x^2-4x-6 | | 3(3x-3)=-45 | | 8(x+2)+4=0 | | x^2-20+100=0 | | 3(4b+2)=42 | | 12-7x=72-42x | | -5x+2(x+3)=-16 | | -3(4n+3)=-45 | | x^2+3xy*4x-12y= | | 4(3-4b)=-52 | | 40=3u-17 | | 4x+1+6=0 | | 3(4+3b)=48 | | 15b-6=-b-12 | | 34+2x+144=-6 | | 4(3-3k)=48 | | 3p(5p-2)= | | -3(4m-3)=45 |

Equations solver categories